Effectiveness Test of Combined Extract Concentrations from Mature and Immature Physic Nut Seeds (Jatropha curcas) on the Mortality of Golden Apple Snail (Pomacea canaliculata) - Rizqullah, Zaidan; Saylendra, Andree; Putri, Widia Eka; Rumbiak, Julio Eiffelt Rossafelt (Jurnal Agroekoteknologi Terapan, 2026)
The golden apple snail (Pomacea canaliculata) is a major pest causing significant damage to rice plants, particularly at the early vegetative stage. The use of chemical pesticides for its control poses negative environmental impacts, thus environmentally friendly alternatives such as botanical pesticides are needed. Physic nut (Jatropha curcas) seeds contain bioactive compounds with pesticidal properties. This study aimed to evaluate the effectiveness of combined mature and immature physic nut seed extract on snail mortality, weight loss, and morphological changes, and to determine the most effective concentration. The experiment used a Completely Randomized Design (CRD) with five treatments: control (0 g/L), 5 g/L, 10 g/L, 15 g/L, and 20 g/L, each with three replications. The results showed that the extract significantly affected all observed parameters. The highest mortality (93%) and weight loss (28.04%) were observed at 20 g/L. Morphological changes included reduced activity, slower response, operculum opening, and eventual body extrusion from the shell leading to death. Higher extract concentrations resulted in greater mortality, weight reduction, and morphological damage. Physic nut seed extract has strong potential as an effective and environmentally friendly botanical pesticide. Keywords: botanical pesticide, golden apple snail, Jatropha curcas, mortality, morphology